INTER-ILEAL-ABDOMINAL DISSECTION IN THE TREATMENT OF PATIENTS WITH LOCALLY ADVANCED BONY AND SOFT TISSUE SARCOMAS - V. A. Derzhavin; V. Yu. Karpenko; A. V. Bukharov; M. V. Ivanova (Исследования и практика в медицине)
Inter-ileal abdominal dissection (IIAD) is one of the most traumatic maiming operations, which implies removal of the lower limb with a single block with an adjacent half of the pelvic ring. Taking into account the low overall incidence of locally advanced bony and soft tissue sarcomas localized in the projection of the pelvic bone and hip joints, and a small number of clinics with suﬃcient experience in performing such operations, modern specialized literature has a limited number of publications on the IIAD.Purpose. Presentation of the experience in the implementation of the IIAD in patients with locally advanced sarcomas of bones and soft tissues.Patients and methods. The analysis of results of treatment of 26 patients with locally advanced sarcomas of bones and soft tissues is presented. There were 14 men (54%), women 12 (46%). Patients with primary malignant tumors of bones 23 (88%) prevailed among patients. Depending on the morphological structure, 16 (61%) had chondrosarcoma, 4 (15%) had osteosarcoma and 3 (11%) had a malignant ﬁbrous histiocytoma. Three (11%) patients had locally advanced softtissue sarcomas. In 2 (7.5%) synovial sarcoma and in one (3.5%) malignant tumor from the shells of peripheral nerves. The primary tumor process was in 21 (81%) patients. The clinical stage was established as IIb in 14 (54%), Ib in 3 (11%), IVa 1 (3.5%) and IVb in 3 (11%) patients, respectively.Results. The average duration of the operation was 4.1 hours (2.7–6 hours). The volume of intraoperative blood loss is 3400 ml (500–9000 ml). The margin of resection was evaluated as positive in 4 (15%) patients. The recurrence of the tumor after  the IIAD performed by us was in 4 (15%) patients with a negative edge of R0 resection.Conclusions. Postoperative complications were noted in 5 (19%) patients. Four (80%) had wound purulent-septic com-plications: partial ﬂap necrosis — 2, total necrosis of the ﬂap — 1, edge necrosis of the wound — 1 patient. The overall 5-year survival rate of patients treated in the clinic by the treatment was 40%. The results of the functional status of patients after  the operation were 45% on the MSTS scale, which correlates with the data of other authors.